EFEKTIVITAS DAN PENGARUH MODEL PEMBELAJARAN INKUIRI PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - Anam, Rif’at Shafwatul (Universitas Pendidikan Indonesia, 2015)
This purpose of this study wants to know how the effectiveness, and the effect inquire learning with experiment method in science lesson to elementary school. The methodology in this study uses a One Group pre-test post-test design. Participants in this study are 25 students. The instrument had a two aspect that is cognitive ability, and science processes skills. The result showed that inquire learning in this study has a medium effective and shows the significant between before and after using the inquire learning in the two aspect to this study.Keywords: inquire learning, cognitive ability, science process skills.